Analisis Rantai Pasok Komoditas Cengkih Di Desa Rerer Kecamatan Kombi Kabupaten Minahasa - Kalumata, Joyner Edward Matthew; Tambas, Jane Sulinda; Ruauw, Eyverson (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the supply chain and product flow, financial flow and information flow of cloves in Rerer Village. The research was carried out for 3 to 4 months. The research location was carried out in Rerer Village, Kombi District, Minahasa Regency. was chosen because it is one of the clove-producing areas. The data collection method uses primary data obtained directly through observation and in-depth interviews with informants using questionnaires, then uses secondary data obtained from literature books, research journals and/or articles or from agencies concerned with research. The research sampling method was by using Snowball Sampling with the number of samples in the study as many as 25 farmer respondents and 2 collector traders respondents. The results show that the supply chain moves from upstream to downstream with the flow of goods from farmers as producers to collectors and distributed to factories.